African, Lusophone, and Afro-Hispanic cultural dialogue - Agawu-Kakraba, Yaw B., 1960-; Aggor, F. Komla (Francis Komla), 1959- (Cambridge Scholars Publishing, 2018)
African, Lusophone, and Afro-Hispanic Cultural Dialogue is a collection of essays of broad historical and geographic scope that advances analytical perspectives regarding a highly transcultural and changing African continent enmeshed in the vestiges of slavery and colonialism and the complex dynamics of post-colonialism. Mostly grounded in literary studies, the essays discuss the interconnections between Africa and its Lusophone and Afro-Hispanic diaspora. Particular focus is given to how they relate to the politics of identity and assimilation, migration and displacement, the concept of "nation", Eurocentrism and racial essentialisms, as well as Black aesthetics.